An Analysis of The Effectiveness and Practicality by Using Constructivism LKPD Assisted With a Flipcreator - Rukmana, Musma; Watung, Fernando Andre; Hasmiati, Hasmiati; Agustina, Tika Putri (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
Abstract: The aim in conducting this research is to analyze the effectiveness and practicality of using constructivist LKPD assisted by Flipcreator, which has previously been developed and found the valid criteria. The research method referred to the RD development model, namely ADDIE: analysis, design, development, implementation, and evaluation. The research subjects consisted of 24 students and 1 biology subject teacher. The instruments used are student evaluation sheets to see the effectiveness of data, students' and teacher' response questionnaire sheets, and learning implementation observation sheets to see practicality data. From the data analysis, the following results were obtained: (1) The effectiveness test showed that the constructivist LKPD assisted by Flipcreator was effectively used in the learning process, with 91.67% of students' learning completeness being fulfilled; (2) in the practicality test, a positive response was obtained from teachers and students of 100%, which was in the very strong category, as well as the results of observations of learning implementation, which showed that all aspects observed in the learning process were fully implemented with a total mean of 1.52. These results showed that the constructivist LKPD assisted by Flipcreator is effective and practical to use in the classroom learning process. Keywords: student’s worksheet, constructivism, flipcreator